TURKISMS IN THE RUSSIAN LANGUAGE: HISTORICAL AND FUNCTIONAL ASPECT - Raximova Zarifa Abduraximovna, (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article analyzes the formation, historical development, and present-day usage of Turkisms in the Russian language. As a result of long-standing political, trade-economic, and cultural contacts with Turkic peoples, a significant number of words of Turkic origin have entered Russian vocabulary. The article examines the ways Turkisms were borrowed into Russian, their semantic transformations, and stylistic functions. In addition, the role of Turkisms found in everyday speech, fiction, and publicistic texts is considered, with attention paid to their position in both active and passive lexical layers. The study employs historical-linguistic and comparative analysis methods. The article aims to determine the role and significance of Turkic languages in enriching the Russian lexicon. Special attention is given to the use and importance of Turkic vocabulary in the works of the Russian writer L. N. Tolstoy. The authors analyze the usage and meanings of Turkic words and conduct a comprehensive comparative study of the number of such words employed in Tolstoy’s Russian novels.